Education and the end of poverty: towards the fulfillment of the objectives and goals of sustainable development - Carlos Julio Carchi-Cuenca; Jorge Antonio Villacis-Salcedo (Maestro y Sociedad, 2018)
The 2030 Agenda has among its fundamental purposes to end poverty in all its forms and dimensions as an indispensable condition for all human beings to realize their potential with dignity and equality, to achieve this goal many efforts and resources are devoted to whole world and especially in the so-called developing countries, including Ecuador. Access to quality education as well as being considered by various scholars as an important indicator for measuring poverty is one of the most important ways to eliminate it. This article, based on the bibliographical analysis, addresses the relationship between poverty and education and assesses the contribution that poverty can and should make to the fulfillment of the objective of sustainable development number 1.